The stem cell growth factor receptor KIT is not expressed on interstitial cells in bladder. Issue 6 (20th December 2016) - Gevaert, Thomas; Ridder, Dirk De; Vanstreels, Els; Daelemans, Dirk; Everaerts, Wouter; Aa, Frank Van Der; Pintelon, Isabel; Timmermans, Jean‐Pierre; Roskams, Tania; Steiner, Clara; Neuhaus, Jochen
Abstract: The mast/stem cell growth factor receptor KIT has long been assumed to be a specific marker for interstitial cells of Cajal (ICC) in the bladder, with possible druggable perspectives. However, several authors have challenged the presence of KIT + ICC in recent years. The aim of this study was therefore to attempt to clarify the conflicting reports on KIT expression in the bladder of human beings, rat, mouse and guinea pig and to elucidate the possible role of antibody‐related issues and interspecies differences in this matter. Fresh samples were obtained from human, rat, mouse and guinea pig cystectomies and processed for single/double immunohistochemistry/immunofluorescence. Specific antibodies against KIT, mast cell tryptase (MCT), anoctamin‐1 (ANO1) and vimentin were used to characterize the cell types expressing KIT. Gut (jejunum) tissue was used as an external antibody control. Our results revealed KIT expression on mast cells but not on ICC in human, rat, mouse and guinea pig bladder. Parallel immunohistochemistry showed KIT expression on ICC in human, rat, mouse and guinea pig gut, which confirmed the selectivity of the KIT antibody clones. In conclusion, we have shown that KIT + cells in human, rat, mouse and guinea pig bladder are mast cells and not ICC. The present report is important as it opposes the idea that KIT + ICC are present in bladder. In this perspective, functional concepts of KIT + ICC being involved in sensory and/or motor aspects of bladder physiology should be revised.